2012
DOI: 10.1007/s11250-012-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a field strain of Brucella abortus from RB51-vaccinated- and brucellosis-seronegative bovine yearlings that calved normally

Abstract: A study was carried out in Pichucalco, Chiapas (Mexico) to determine whether recently calved cows or those that aborted shed Brucella. Serological diagnosis of brucellosis was made in all animals (209). Six of the cows that calved normally and two that aborted underwent a bacteriological study of milk and vaginal exudate. Brucella abortus was isolated from vaginal exudate samples in two 3- to 4-year-old seronegative first-birth cows that had calved normally. This was confirmed through bacteriological identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The two farms included in this study showed cases of abortion after routine testing with RBPT, BAPAT and CFT with negative results. Identification of seronegative carriers can be achieved by analyzing vaginal exudates or milk [ 7 ]. Detection of Brucella spp.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…The two farms included in this study showed cases of abortion after routine testing with RBPT, BAPAT and CFT with negative results. Identification of seronegative carriers can be achieved by analyzing vaginal exudates or milk [ 7 ]. Detection of Brucella spp.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Indeed, the protection afforded to non-immune animals by the presence of sufficient numbers of immune individuals, known as “herd immunity” ( Figure 6 ) is threatened if the immune status of the herd is low. That is, inefficient vaccines may promote a fertile niche in weakly immune hosts allowing virulent Brucella to be transmitted though vaccinated animals (Herrera-López et al, 2010, 2011; Arellano-Reynoso et al, 2013). In curse this will increase the number of secondary infections.…”
Section: Coping With Brucellosismentioning
confidence: 99%
“…For example, if the anti- Brucella vaccine fails to generate immunity in a fraction p of those animals vaccinated, then to achieve herd immunity we need to vaccinate a proportion of individuals equivalent to R 0 - 1/ R 0 (1 - p ) ( Figure 7 ). Hence, if p is too big it may be impossible to eradicate brucellosis as it has been the case in many countries where vaccines of low-efficacy have extensively been used (Blasco et al, 1993; Moreno, 2002; Vargas, 2002; Blasco and Moriyón, 2005; Arellano-Reynoso et al, 2013; Chand and Chhabra, 2013; Denisov et al, 2013; Hou et al, 2013; Jiang et al, 2013; Li et al, 2013; Oseguera-Montiel et al, 2013; Rubach et al, 2013). …”
Section: Coping With Brucellosismentioning
confidence: 99%
See 1 more Smart Citation
“…Brucella abortus was isolated in119 milk samples from seronegative cows and the isolates belonged to biovars 2, 3, and 9. In Mexico, the field strain of B abortus with a smooth phenotype was reported to have been isolated from the vaginal exudates of two cows, vaccinated with reduced-dose RB51, which had calved normally and were seronegative [23].…”
Section: Geographical Distribution In Animalmentioning
confidence: 99%